INVESTING IN HUMAN CAPITAL AND ITS IMPACT ON IMPROVING PERFORMANCE AN EXPLORATORY RESEARCH IN THE TEXTILE FACTORY IN BABYLON - Dr. Samah Muyyad Mahmood, Zaynab Jawad Ubeid (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research aims to discuss the impact of investment in human capital with its components (training, education, knowledge management, skills development) on improving the performance of textile factory/ Babylon. The questionnaire was used as a tool to collect data and information related to the research. It was subjected to the scale of validity and reliability and distributed to a sample of the research consisted of (150) managers. The data of the research was analyzed according to the exploratory factor analysis using the program (SPSS V. 22) in order to test the scale of the first axis: Investing in human capital and its dimensions (training, education, knowledge management, and skills development), the second axis: Improving performance and its dimensions (success, flexibility, creativity, and quality). However, the hypothesis test, the Spearman correlation coefficient, and the regression analysis were used. The statistical methods yielded a number of conclusions, perhaps the most prominent of which is the lack of clarity in the interest in training activity, innovation, quality, and success in the factory due to the lack of clarity of the state's vision towards the industrial sector, and the lack of support for the local (national) product for not imposing certain specifications for imported goods, and even if this is done, financial and administrative corruption prevents that, especially in Iraqi ports. Therefore, the main recommendation focused on presenting a set of practical proposals that aim at the possibility of improving performance, including those related to laws and legislation of the Ministry of Industry and Minerals and others related to training courses.